Transregional and Regional Elites – Connecting the Early Islamic Empire - Heidemann, Stefan (Studies in the History and Culture of the Middle East, 2020)
To integrate the regions of the early Islamic Empire from Central Asia to North Africa, transregional and regional elites of various backgrounds were essential. The papers analyze elite groups, their structures and networks, within selected regions across geographical, religious and social boundaries. While each region seems to be different, certain common patterns of governance and interaction made the largest empire of Late Antiquity work